How info-firms use big data to target customers. Issue 6 (19th November 2018) - Dolfsma, Wilfred; Van der Eijk, Rene
Abstract : Purpose: The purpose of this paper is to review and assess the different strategies that what we call Info-firms can deploy in the markets that they serve. In many markets, a firm's competitive advantage is derived from its information position. Firms that actively and extensively collect customer information may develop a number of strategies to increase their competitiveness. We refer to such firms as info-firms – for some firms, this is all that they do: collect and sell data about consumers. Info-firms can target either customers or other firms, and they target either existing or adjacent markets. A 2 × 2 matrix characterizing strategies is introduced. Some strategies are known, but their effects are more pronounced on online markets because of the overwhelming amount of data available, while other strategies that are discussed are new. The strategies that info-firms develop and use change the dynamics in value chains substantially. The strategies adopted affect the market and value chain dynamics and determine which parties in the market are likely to benefit (most). Design/methodology/approach: This is a conceptual paper. Findings: The strategies that info-firms develop and use change their dynamics in value chains substantially. Some strategies are known, but their effects are more pronounced on online markets because of the overwhelming amount of data available, while other strategies are new. Research limitations/implications: Drawing on an economic theory, an evaluation of the strategies that info-firms develop is offered, identifying which parties stands to gain the most. Practical implications: The effects of the use of strategies used by info-firms have been largely overlooked, and yet, strategies adopted affect the market and value chain dynamics and determine which parties in a market are likely to benefit (most). Originality/value: The classification of strategies that info-firms can develop, and the likely effects on the market dynamics and economic prospects of different market players has not been discussed in the literature so far. A comprehensive and novel perspective is offered.